2020
DOI: 10.1029/2020tc006231
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Thermochronologic Constraints on the Cenozoic Tectonic Development of the Northern Indo‐Burma Ranges

Abstract: The~1,500-km-long, north trending Eastern Flanking Belt of the Himalayan-Tibetan orogenic system is located along the eastern margin of the Indian subcontinent. Although the belt is a key element of the Cenozoic India-Asia collisional zone, its tectonic evolution remains poorly understood. This lack of knowledge has impacted our ability to differentiate between competing hypotheses for the evolution of the India-Asia collision. To address this problem, we integrate constraints on the structural framework and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 198 publications
(393 reference statements)
0
22
0
Order By: Relevance
“…Tectonics late Eocene thrusting in the Eastern Himalayan collision zone north of the IBR (Haproff et al, 2020), which these studies also attributed to the India-Asia collision. This together leads us to propose that the latest Eocene-middle Oligocene unconformity from this study was induced by the onset of the collision of India and Greater Burma with Asia in the Eastern Himalayas.…”
Section: 1029/2020tc006413mentioning
confidence: 65%
See 3 more Smart Citations
“…Tectonics late Eocene thrusting in the Eastern Himalayan collision zone north of the IBR (Haproff et al, 2020), which these studies also attributed to the India-Asia collision. This together leads us to propose that the latest Eocene-middle Oligocene unconformity from this study was induced by the onset of the collision of India and Greater Burma with Asia in the Eastern Himalayas.…”
Section: 1029/2020tc006413mentioning
confidence: 65%
“…To the north, the transition from the BT to the Eastern Himalayan orogen is defined by the intersection of the Sagaing Fault and the IBR (Lin et al, 2019; Mitchell, 2017; Mitchell et al, 2012). However, it is unclear how much of the northern extension of the BT (i.e., Greater Burma) was shortened, subducted, and underthrust in the Eastern Himalayan Syntaxis during its northward motion (Haproff et al, 2019, 2020; Morley et al, 2020; Westerweel et al, 2019). At present, the orogen bends from ~E‐W to ~NW‐SE at the Eastern Himalayan Syntaxis (Figure 1a).…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Red rectangle showing the area of (b). (b) Regional geological map of the easternmost part of the Himalayan orogen after Haproff, Odlum, Zuza, Yin, and Stockli (2020). Dibang valley is shown in no.1 red oval box, while our present study area in Lohit Valley is shown in no.…”
mentioning
confidence: 86%